Management and Distribution Clean Water Technology for Village Tour Mountain Buthak Purworejo - Suyitno Suyitno; Nurul Qomariyah; Siska Desy Fatmaryanti; Yuli Widiyono; Faruq Iskandar (Edumedia Solution, 2022)
This community service activity aims to develop a tourist village through the distribution of clean water in the Gunung Buthak tourist village of Tlogokotes Bagelen , Purworejo , Central Java. The participants in this activity were members of the Pokdarwis awareness group for Mount Buthak tourism. This activity consists of three stages, namely planning, implementation, and evaluation. The method applied is counseling and workshops on clean water management.The results of the evaluation show that the community service activities have been carried out properly. The participants were also enthusiastic and actively participated in this activity. This is shown from the evaluation results which show an increase in community knowledge about the use and distribution of clean water as a form of village tourism marketing. With the implementation of this activity, it is hoped that Mount Buthak tourism can be widely known by tourists so that many tourists visit Mount Buthak so as to increase the economic value and welfare of the local community.